The Library of Petrus Gotfart de Corona, Rector of the University of Vienna in 1473. (23rd February 2019) - Papahagi, Adrian
Abstract: Petrus Gotfart from Braşov (Corona in Latin) is the only medieval layman from Transylvania whose books have come down to us. This scholar taught Aristotle at the university of Vienna between 1456‐76, and in 1473 served as rector of that institution; he died in 1476, leaving most of his books to his university. Four manuscripts and four incunabula are still in Vienna, but one incunabulum bearing the ownership note of the Ducal College ended up in Oxford. Another incunabulum travelled to Transylvania with its binder, who had worked for Petrus Gotfart. Furthermore, in 1460 Petrus had copied Basil the Great's Ad adolescentes, now part of a miscellaneous manuscript in Melk. These books disclose the interests of a Central European scholar, and give insight into the peregrinatio academica, the circulation of books, and the growth and dissolution of private libraries in the late Middle Ages.